2020
DOI: 10.1108/qram-02-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Management accounting use in micro and small enterprises

Abstract: Purpose The purpose of this paper is to explore if and how micro and small firms apply management accounting (MA) techniques. Design/methodology/approach The study is based on 36 semistructured interviews with micro and small firm owners/managers in Mexico. Content analysis is used to identify how these enterprises use MA tools. Findings Micro and small firms consistently use MA tools. Most of them have some sort of planning, set objectives, have a costing system – even if budgeting is unusual – and use on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…According to Nartey & van der Poll (2021), innovative management accounting practices is also found to influence sustainability of manufacturing small and medium enterprises. Similarly, Alvarez et al (2021;Ahmad & Zabri, 2016;Ruiz & Collazzo, 2021) found that management accounting practice positively affects MSMEs performance.…”
Section: Figure 1 Number Of Msmes In West Java Province 2016 -2021mentioning
confidence: 93%
“…According to Nartey & van der Poll (2021), innovative management accounting practices is also found to influence sustainability of manufacturing small and medium enterprises. Similarly, Alvarez et al (2021;Ahmad & Zabri, 2016;Ruiz & Collazzo, 2021) found that management accounting practice positively affects MSMEs performance.…”
Section: Figure 1 Number Of Msmes In West Java Province 2016 -2021mentioning
confidence: 93%
“…The higher the growth of the company, the greater the need for funds needed by the company. (Najera Ruiz & Collazzo, 2021).…”
Section: The Effect Of Corporate Growth On the Capital Structure Of H...mentioning
confidence: 99%
“…Sandino (2007) finds that most early growth retail firms in their study adopted basic MCS for planning, standards and basic operational support. Recent research on micro and small firms also notes a prioritization of basic management accounting tools designed to aid in planning, setting objectives, costing and monitoring performance (Najera Ruiz and Collazzo, 2021). The results of a study of early-stage start-up companies by Davila and Foster (2007) similarly indicate an early prioritization of the formalization of financial planning processes with more sophisticated control systems, including financial evaluation systems that can be adopted at a later stage.…”
Section: Contextual Background and Literature Reviewmentioning
confidence: 99%
“…The literature finds that larger firms with sophisticated technologies and high diversity place greater emphasis on formal and sophisticated controls to minimize the loss of control and obtain relevant information in planning, controlling and decision-making (Abdel-Kader and Luther, 2008; Management control systems Bruns and Waterhouse, 1975;Chenhall, 2006;Khandwalla, 1972). Small firms have been found to differ from their larger peers in the degree of formalization and types of systems used (Sian and Roberts, 2009;Shields and Shelleman, 2016;Najera Ruiz and Collazzo, 2021), such that the efficient generation of essential financial and accounting information poses a more formidable challenge for smaller firms (Halabi et al, 2010;Lavia L opez and Hiebl, 2015;Senftlechner and Hiebl, 2015). These differences are due to several variables, including geographical reach, degree of centralization, diversification (Khandwalla, 1972;Groot and Merchant, 2000;Chenhall, 2003) and available resources (Jänkälä and Silvola, 2012;Krumwiede, 1998;).…”
Section: Contextual Background and Literature Reviewmentioning
confidence: 99%